(3Qhfb GdeLGdSs - (3YeQ GdSeQbfOj , YeQ Hf GdMSf GdfjSGHhQj GdMfaj, CHh MaU,J (B840 (3g` s ((3YjSi Hf fYeGf Hf YKeGf GdSdWGfHhdi s)
(3ChdgG (B:s
(3GdHGH GdChd ai GKHGJ GdEdhgjI ddg YR hLd GdMcGjI GdChdi (B: (3bGd GdTjN QMeg Gddg SeYJ QLdkG ef RgGO fjSGHhQ s
(3BNQgG (B:s
(3abGd dg Edi Cjf abGd Edi HjJ Gddg GdPi gh QHi abGd dg Gjf GdRGO hGdQGMdg Je cJGH Qhfb GdeLGdS s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3ai ChdgG agQS hHgG fbU ai ehVY hGMO HChdgG s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs